Public Pension Reform : A Primer - Jousten, Alain (IMF Working Papers; Working Paper ;, 2007)
The present paper reviews key issues in pension design and pension reform encountered all across the world. The paper heavily refers to the recent U.S. Social Security reform debate in general and to the Personal Retirement Accounts proposal in particular. A particular emphasis is put on annuitization and risk-taking in the economy. Our discussion signals some inadequacy of the proposed measures with respect to the goals of viability of the system and individual financial security during retirement.